Post-translational modifications of p65: state of the art - Sun, Xutao; Cao, Shuo; Mao, Caiyun; Sun, Fengqi; Zhang, Xuanming; Song, Yunjia (Frontiers in Cell and Developmental Biology, 2024)
P65, a protein subunit of NF-κB, is a widely distributed transcription factor in eukaryotic cells and exerts diverse regulatory functions. Post-translational modifications such as phosphorylation, acetylation, methylation and ubiquitination modulate p65 transcriptional activity and function, impacting various physiological and pathological processes including inflammation, immune response, cell death, proliferation, differentiation and tumorigenesis. The intricate interplay between these modifications can be antagonistic or synergistic. Understanding p65 post-translational modifications not only elucidates NF-κB pathway regulation but also facilitates the identification of therapeutic targets and diagnostic markers for associated clinical conditions.